THE CORRELATION OF QIYĀM AL-LAIL WITH HUMAN IMMUNITY IN HADITH PERSPECTIVE - Magfirah, St. (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2020)
The focus of this research is correlation of qiyām al-lail with human immunity in hadith perspective. The problem statements are: 1) what is the quality of hadith of qiyām al-lail?, and 2) what is the correlation of qiyām al-lail with human immunity in hadith perspective? The aims of this research are: 1) to describe the quality of qiyām al-lail hadith, and 2) to explore the correlation of qiyām al-lail with human immunity in the hadith perspective. The method used in this writing is analytical method (taḥlīlī). Some of approaches used are hadith science and health science. The findings of this research show that : 1) the quality of hadith is hasan because all of sanad from al-Tirmiżi’s book have capability (ḍabit and ‘adil ). Therefore, this hadith can be a standard to qiyām al-lail, and 2) qiyām al-lail and human immunity have a correlation in hadith perspective, as mentioned by Muslim scholars and findings of scientists.